Therapeutic Vaccination Strategies - Walden, P.; Sterry, W.; Hennekes, H. (Ernst Schering Foundation Symposium Proceedings, 2000)
The induction of immune responses against tumor cells by vaccination is rapidly evolving as a therapeutic modality with new potentials for the treatment of cancer. It is based on the fact that our immune system can identify tumor cells and, once activated, is capable of developing specific immunity against the neoplastic cells. Numerous observations and intense research clearly document the major contribution of the immune system to the prevention of cancer. And there are many re ports of patients suffering from malignant melanoma or other tumors who mount a spontaneous immune response against their tumor cells that results in tumor regression. Based on the recent advances in our understanding of the compo nents of our immune system, their interactions and the regulation of immune responses, we are now able to design vaccination strategies that induce or enhance cell-mediated immunity against tumors. A ma jor advancement came with the identification and characterization of relevant tumor antigens, which are suitable target structures for anti-tu mor immune response. First clinical trials using such vaccine strategies have yielded encouraging results in patients. However, in spite of many reported cases of successful therapy of cancer by vaccination many patients still do not experience relief after such treatments. These initial clinical trials and the accompanying investigations have revealed a number of important results that indicate the direction of future re search and development in the field